2021
DOI: 10.1021/acs.inorgchem.1c02667
|View full text |Cite
|
Sign up to set email alerts
|

A Series of High-Nuclear Gadolinium Cluster Aggregates with a Magnetocaloric Effect Constructed through Two-Component Manipulation

Abstract: The serialized expansion of high-nuclear clusters usually includes the controlled variable method and changes only a single variable. However, changing both variables will greatly increase the complexity of the reaction simultaneously. Therefore, the use of a two-component regulation reaction is rare. Herein, we used a diacylhydrazone ligand (H 4 L 1 ) with multidentate chelating coordination sites for the reaction with Gd(NO 3 ) 3 •6H 2 O under solvothermal conditions to obtain an example of 16-nucleus discsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In 2020, the authors’ group obtained an example of a double cage-like dysprosium cluster Dy 60 by reacting a polydentate chelate-coordinated bisacylhydrazone ligand with Dy­(OAc) 3 ·4H 2 O under solvothermal conditions . Although tremendous progress has been made, the design and synthesis of high-nucleation lanthanoid clusters with specific shapes and linkages are still stagnant and currently limited to common shapes, such as cages, tubes, and wheels. The main reasons are the large radius of lanthanoid metal ions, complex coordination modes, difficulty in forming stable coordination bonds with metal ions, difficulty in controlling the hydrolysis process, diverse hydrolysis products, and self-assembly processes interfered by multiple templates. , Therefore, designing and synthesizing high-nucleation lanthanoid clusters with special shapes are still extremely difficult, and the progress is slow. , …”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the authors’ group obtained an example of a double cage-like dysprosium cluster Dy 60 by reacting a polydentate chelate-coordinated bisacylhydrazone ligand with Dy­(OAc) 3 ·4H 2 O under solvothermal conditions . Although tremendous progress has been made, the design and synthesis of high-nucleation lanthanoid clusters with specific shapes and linkages are still stagnant and currently limited to common shapes, such as cages, tubes, and wheels. The main reasons are the large radius of lanthanoid metal ions, complex coordination modes, difficulty in forming stable coordination bonds with metal ions, difficulty in controlling the hydrolysis process, diverse hydrolysis products, and self-assembly processes interfered by multiple templates. , Therefore, designing and synthesizing high-nucleation lanthanoid clusters with special shapes are still extremely difficult, and the progress is slow. , …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Although the exploration of the self-assembly mechanism of lanthanide clusters is still at the initial stage, we have made a series of progresses in this field. [28][29][30][31][32][33][34][35][36][37] In 2018, we were the first to use HRESI-MS to track the self-assembly process of triangular-shaped dysprosium clusters with toroidal magnetic moments. 28 Furthermore, we were the first to use crystallography combined with the HRESI-MS technique to trace the formation mechanism of the high-nuclearity lanthanide cluster Dy 10 with double relaxation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…High-nucleation lanthanide clusters with unique shapes, attractive structures, and superior characteristics are actively continuously being designed and synthesized. To date, different lanthanide clusters with various shapes, linkages, and nuclei have been prepared, and their applications in the fields of molecular magnetism, luminescence, sensing, and catalysis have been successfully expanded. Although great progress has been made, high-nucleation lanthanide cluster design and synthesis have also been aided by a number of assembly methods. In 2021, our group first proposed an out-to-in growth mechanism for designing and synthesizing a series of discoid lanthanide clusters . Afterward, we found that the outside-in growth mechanism can be effectively manipulated by regulating the reaction solvent or anion or by adding a second ligand, and we obtained a series of lanthanide clusters with different shapes. , However, the out-to-in growth mechanism is only suitable for bulky organic ligands that have strong chelating ability and numerous coordination sites. When the organic ligands in the reaction system have small volumes, poor chelating ability, and few coordination sites, the hydrolysis conditions and anionic template become a major factor in controlling the formation of lanthanide clusters. ,, Ligand-mediated hydrolysis of lanthanide ions first undergoes tight binding between Ln­(III) ions and water to obtain hydrolysis products with various shapes (template precursors), such as linear {Ln 2 (μ 2 -OH)}, triangular {Ln 3 (μ 3 -OH)}/{Ln 3 (μ 3 -OH) 2 }, tetrahedral {Ln 4 (μ 3 -OH) 4 }, trigonal bipyramidal {Ln 5 (μ 3 -OH) 6 }, square pyramidal {Ln 5 (μ 3 -OH) 4 (μ 4 -O)}, and octahedral {Ln 6 (μ 3 -OH) 8 (μ 6 -O)}. ,, The hydrolysates are then captured by ligands for assembly to form lanthanide clusters with specific shapes. Therefore, manipulating lanthanide-ion hydrolysis to produce certain template motifs with specific assembly is an effective strategy for constructing lanthanide clusters with specific shapes and linkages .…”
Section: Introductionmentioning
confidence: 99%